Local blood coagulation drives cancer cell arrest and brain metastasis in a mouse model - Feinauer, Manuel; Schneider, Stefan W.; Bergmeister-Berghoff, Anna Sophie; Robador Arteta, José Ramon; Tehranian, Cedric; Karreman, Matthia A.; Venkataramani, Varun; Solecki, Gergely; Grosch, Julia Katharina; Gunkel, Katharina; Kovalchuk, Bogdana; Mayer, Frank Thomas; et al. (Blood, 2020)
Clinically relevant brain metastases (BM) frequently form in cancer patients, with limited options for effective treatment. Circulating cancer cells must first permanently arrest in brain microvessels to colonize the brain, but the critical factors are not well understood. Here, in vivo multiphoton laser-scanning microscopy (MPLSM) of the entire brain metastatic cascade allowed unprecedented insights into how blood clot formation and von Willebrand factor (VWF) deposition determine the arrest of circulating cancer cells and subsequent brain colonization in mice.
Gesehen am 12.01.2021